The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1055/s-2007-969072
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Studies on Leaves ofWithania somnifera

Abstract: Anti-inflammatory activity and protective effect against CC!4-induced hepatotoxicity of alcoholic extract of leaves of Withania somnifera have been assessed. The leaves were found to possess marked effects in subacute inflammation and hepatotoxicity. A comparison of the anti-inflammatory properties revealed the extract at 1 g/kg dose to be as active as 50 mg/kg of phenylbutazone and 10 mg/kg of hydrocortisone. The protective effect of the extract at 1 glkg dose against CCI4induced hepatotoxicity was comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…The role of W. somnifera to modulate a variety of biological responses has been reported [9,10]. It has found extensive use in many indigenous preparations for its medicinal values such as anti-ageing, aphrodisiac, cardio tonic, antiperoxidative [9], anti-inflammatory [11], antitumor [12] , antioxidant, immunomodulatory, hemopoietic, and rejuvenating properties [13]. The chemistry of this plant has been extensively studied and over 35 chemical constituents have been identified, extracted, and isolated.…”
Section: Introductionmentioning
confidence: 99%
“…The role of W. somnifera to modulate a variety of biological responses has been reported [9,10]. It has found extensive use in many indigenous preparations for its medicinal values such as anti-ageing, aphrodisiac, cardio tonic, antiperoxidative [9], anti-inflammatory [11], antitumor [12] , antioxidant, immunomodulatory, hemopoietic, and rejuvenating properties [13]. The chemistry of this plant has been extensively studied and over 35 chemical constituents have been identified, extracted, and isolated.…”
Section: Introductionmentioning
confidence: 99%
“…The role of W. somnifera to modulate a variety of biological responses has been reported (Ziauddin et al, 1996;Mishra et al, 2000;Davis and Kuttan, 2000). It has found extensive use in many indigenous preparations for its medicinal values such as anti-ageing, aphrodisiac, cardio tonic, thyroregulatory, antiperoxidative (Mishra et al, 2000), anti-inflammatory (Sudhir et al, 1986), antitumor (Sharada et al, 1996), antistress, antioxidant, immunomodulatory, hemopoietic, rejuvenating properties, etc. (Thakur et al, 1989.…”
mentioning
confidence: 99%
“…Anbalgan and Sadique (1981) and Sudhir et al (1985) also found significant anti-inflammatory activity of W. sornnifcm against carrageenin-induced rat paw oedema. Singh (1979) reported the antiinflammatory activity of W. sornnifem on carrageenin-induced paw oedema at the dose of 500 mgfkg.…”
Section: Methodsmentioning
confidence: 91%